2017
DOI: 10.1371/journal.pone.0188297
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle intervention program in deprived obese adult patients and their non-deprived counterparts

Abstract: IntroductionAlthough it is known that the prevalence of obesity is high in deprived patients, the link between deprivation and obesity, and the impact of deprivation on compliance and efficacy of a lifestyle intervention program are not known.Materials and methodsDeprivation was assessed in 40 patients (23 Females, mean±SD age: 49±17 years) from the diabetology department and 140 patients (101 Females, age: 50±15 years) from the nutrition department of Bordeaux University hospital. Eighty-seven patients suffer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Differences in living conditions are related to different capabilities and participation opportunities and might therefore influence health outcomes and health care decisions. A recently published study reported that more deprived patients with obesity have a more serious disease compared to less deprived patients [22]. A previous APV analysis indicated that not all obese individuals demonstrate cardiovascular risk factors [23].…”
Section: Discussionmentioning
confidence: 98%
“…Differences in living conditions are related to different capabilities and participation opportunities and might therefore influence health outcomes and health care decisions. A recently published study reported that more deprived patients with obesity have a more serious disease compared to less deprived patients [22]. A previous APV analysis indicated that not all obese individuals demonstrate cardiovascular risk factors [23].…”
Section: Discussionmentioning
confidence: 98%